Mentoring to develop research selfefficacy, with particular reference to previously disadvantaged individuals - Schulze, S. (Koers, 2010)
The development of inexperienced researchers is crucial. In response to the lack of research self-efficacy of many previously disadvantaged individuals, the article examines how mentoring can enhance the research self-efficacy of mentees. The study is grounded in the self-efficacy theory (SET) – an aspect of the social cognitive theory (SCT). Insights were gained from an in-depth study of SCT, SET and mentoring, and from a completed mentoring project. This led to the formulation of three basic principles. Firstly, institutions need to provide supportive environmental conditions that facilitate research selfefficacy. This implies a supportive and efficient collective system. The possible effects of performance ratings and reward systems at the institution also need to be considered. Secondly, mentoring needs to create opportunities for young researchers to experience successful learning as a result of appropriate action. To this end, mentees need to be involved in actual research projects in small groups. At the same time the mentor needs to facilitate skills development by coaching and encouragement. Thirdly, mentors need to encourage mentees to believe in their ability to successfully complete research projects. This implies encouraging positive emotional states, stimulating self-reflection and self-comparison with others in the group, giving positive evaluative feedback and being an intentional role model.